Pengaruh sifat fisik agregat kasar dan jenis aspal keras terhadap nilai koefisien kekuatan relatif lapisan permukaan dan modulus kekakuan hot rolled asphalt (hra) - Perpustakaan UGM, i-lib ([Yogyakarta] : Pusat Studi Lingkungan Hidup,UGM, 1998)
ABSTRACT(PRIVATE ) This research aims to find out some phenomena concerning with the content, shape, and nominal size of coarse aggregate grains and type of hard asphalt toward the coefficient value of relative strength (al) of surface layer, and the elastic mix stiffness value (Sme) of hot rolled asphalt (HRA) mixture applied as flexible surface layer, which has structural value. This research applies Marshall test for each model of HRA mixture composed from the variety of content (56%, 63%, 70%), shape (rounded, crushed) and nominal size of grain (20mm, 28mm, 35mm) of coarse aggregate, and type of hard asphalt (AC 60-70, AC80-100) as the binding material. The model of HRA crushed mixture with AC 60-70 asphalt will have higher value of al and Sme if within the range of nominal size of 23mm-30mm, it has bigger content. Similarly, this also applies to the model of HRA rounded mixture using AC 80-100 asphalt within the range of nominal size of 34mm-35mm. In addition, the findings also indicate that in the model of HRA crushed mixture and HRA rounded mixture using AC 80-100 asphalt has lower value of al and Sme if within the range of nominal size of 20mm-29mm, they have bigger content. This is similar to the model of HRA crushed mixture and HRA rounded mixture using AC 60-70 asphalt within the range of nominal size of 20mm-22mm, and 32mm-35mm. From these findings the best model of HRA crushed mixture derives, i.e. with 70% coarse aggregate content, optimum 5.36% AC 60-70 asphalt content, and nominal size of 28mm having al value=0.3928 and Sme value=2473.92 MPa. Another best model is 56% coarse aggregate content, optimum 5.66% AC 60-70 asphalt content, nominal size of 35mm having a, value=0.380 I and Sme value=2426.22 MPa. Meanwhile the best model of HRA rounded mixture is 56% coarse aggregate content, optimum 5.36% AC 60-70 asphalt content, nominal size of 20mm having al value of 0.3409 and Sme value=2017.60 Mpa.